(untitled) (Revista de Estudos da Linguagem, 2004)
The aim of this research was to continue the work in articulatory synthesis. Thus, a database was collected, containing the nasal sounds of European Portuguese (EP). This corpus includes the different phonetic contexts for the nasal vowels of EP, focusing on the regional variants. The recordings include voice signal, and, simultaneously,information about glottal source, obtained through an Electroglotograph (EGG). After the signal processing the following parameters were analysed:duration, F0, open quotient, jitter and shimmer. Finally, statistical and inferential analysis was made using the programme SPSS.